2020
DOI: 10.1246/bcsj.20200004
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Primary C–H Bonds in Picolines toward Pyridylthioamides

Abstract: We report a method for coupling of nitroarenes, 2- or 4-methylazaarenes, and elemental sulfur to afford (2-pyridyl)aryl thioamides. Good tolerance of functionalities was observed, including primary and secondary amines, bromo, iodo, ester, and boronic ester groups. Thioamides derived from pyrazole, thiazole, quinoline, quinoxalines, and azoles were obtained in good yields, showing the compatibility of heterocycles. This appears to be a general method to obtain pyridyl thioamides in one step from commercial, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mechanistic studies revealed that in situ generated S 3 of aryl thioamides 52 has been developed by Phan, Nguyen and coworkers in 2020. 34 Various methylazaarenes 50 such as methylpyrazole, methylthiazole, methylquinoline, methylquinoxalines, and methylazoles were successfully converted to the corresponding aryl thioamides 52 under argon at 120 °C (Scheme 15).…”
Section: C-h Bond Thiolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies revealed that in situ generated S 3 of aryl thioamides 52 has been developed by Phan, Nguyen and coworkers in 2020. 34 Various methylazaarenes 50 such as methylpyrazole, methylthiazole, methylquinoline, methylquinoxalines, and methylazoles were successfully converted to the corresponding aryl thioamides 52 under argon at 120 °C (Scheme 15).…”
Section: C-h Bond Thiolationmentioning
confidence: 99%
“…A multi-component reaction of nitroarenes 50 , 2- or 4-methylazaarenes 51 , and elemental sulphur in the presence of DABCO (1,4-diazobicyclo[2.2.2]octane) for the construction of aryl thioamides 52 has been developed by Phan, Nguyen and coworkers in 2020. 34 Various methylazaarenes 50 such as methylpyrazole, methylthiazole, methylquinoline, methylquinoxalines, and methylazoles were successfully converted to the corresponding aryl thioamides 52 under argon at 120 °C (Scheme 15).…”
Section: Reactions Involving S3˙−in Situ Generated From Elemental Sul...mentioning
confidence: 99%
“…It was previously reported that 6-nitroquinoline could react with electrophiles through a pathway identical to that of N , N -dialkyl-3-nitroanilines. 9 Thus, product 3ha was isolated in 41% yield from the annulation of 6-nitroquinoline and phenyl isothiocyanate 2a under standard conditions.…”
Section: Resultsmentioning
confidence: 99%